Ulcerative colitis and cytokines: a literature review (Research, Society and Development, 2020)
Inflammatory Bowel Diseases (IBD) generally affect young individuals, have a global incidence, representing an important public health problem today. Ulcerative colitis is the most common inflammatory bowel disease, characterized by chronic and diffuse inflammation of the intestinal mucosa, often limited to the colon, presenting as main symptoms abdominal pain and mucosanguinolent diarrhea, substantially compromising the quality of life of the individuals affected by it. Its etiology has not yet been fully clarified, however it has been established that a trigger still unknown triggers, in genetically predisposed individuals, an aberrant immune response that culminates in inflammatory processes. The primary pathophysiological elements that guide the beginning, evolution and, ultimately, resolution of IBDs are the responses of the cytokines that characterize them. The first level of cytokine responses is governed by the differentiation patterns of T cells characteristic of each disease. The aim of this study was to conduct a literature review to gather evidence on the profile of cytokines characteristic of ulcerative colitis. The study was carried out through a literature review, with the survey of scientific evidence in the databases Pub Med, Science Direct and Scopus. Ulcerative colitis classically presented as an inflammatory disease mediated by Th2 cells, which has as characteristic cytokines IL 4, IL 5, IL 13, IL 21 and IL 25, however recent evidence has recognized the existence of significant accommodation between cell activation Th2 and Th1 (IFN γ, IL 2 and TNF α) and the auxiliary participation of Th9, Th17 and Th22 cells and regulatory T cells.